2016
DOI: 10.1002/lary.26401
|View full text |Cite
|
Sign up to set email alerts
|

Malignant otitis externa hospitalizations: Analysis of patient characteristics

Abstract: 2C. Laryngoscope, 127:2328-2336, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 19 publications
4
38
0
1
Order By: Relevance
“…Several hypotheses have been put forth as to the pathophysiology of MOE in patients of advanced age, including poor microcirculation and slow epithelial migration in the external ear canal, which are also associated with diabetic complications. Interestingly, 27.8% of MOE cases are comorbid with hypertension, which is in line with other reports (ranging 52.5%‐76%) . The association between hypertension and MOE requires further investigation.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Several hypotheses have been put forth as to the pathophysiology of MOE in patients of advanced age, including poor microcirculation and slow epithelial migration in the external ear canal, which are also associated with diabetic complications. Interestingly, 27.8% of MOE cases are comorbid with hypertension, which is in line with other reports (ranging 52.5%‐76%) . The association between hypertension and MOE requires further investigation.…”
Section: Discussionsupporting
confidence: 89%
“…The survival rate significantly improved after the introduction of ciprofloxacin and other antimicrobials in the 1990s . In our studies, we found a 2.6% in‐hospital mortality rate, while other larger series reported mortality ranging from 0.5% to 3.7% …”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Although uncommon, NOE has been described in relatively young individuals without diabetes or immunocompromise 13. In fact, the description of NOE as a disease of exclusively older people with diabetes may not be true: between 2002 and 2013, elderly, diabetic patients accounted for only 22.7% of NOE cases 14. The incidence of NOE also appears to be increasing, with a sixfold increase in the number of cases from 1999 to 2013 15…”
Section: Discussionmentioning
confidence: 99%